EMIRATI ENGINEERING STUDENTS’ LEARNING STYLES: A LONGITUDINAL STUDY - Balfaqeeh, Muna; Hassan, Asli; Berkett, Theodore (PEOPLE: International Journal of Social Sciences, 2017)
In the first two years of their undergraduate studies, engineering majors are required to take multidisciplinary courses that are designed to develop their basic skills knowledge, thinking processes and learning strategies among many other subskills necessary for the workforce.This study focuses on the pressing question of whether or not these multi-disciplinary courses at specialized institutions such as the Petroleum Institute have an impact on the students’ long term development of specific learning styles that are beneficial to their career in the oil and gas industry. In this study, the Vark questionnaire was used to study both foundation and senior students’ learning styles to see (1) whether gender has any impact on the students’ learning styles; (2) whether engineering students’ learning styles alter as they progress in their studies, both of which may affect retention and/or progression in their academic levels. The aim of this research is to utilize this information and apply the results of the data in the development of the teaching methods and pedagogies used by the faculty and more specifically in the way they approach engineering students. The paper concludes that there are specific learning styles attributed to engineering students that educators in specialized universities should focus on by adjusting their pedagogy to accommodate them.